2021
DOI: 10.17582/journal.sja/2022/38.1.188.194
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Meat Species by PCR-RFLP Method using Single Set of Degenerative Primers

Abstract: Electrophoresis, chromatography and enzyme-linked immunoassay are common analytical techniques (Hsieh, 2000;Floren et al., 2015). Different muscle proteins are separated by electrophoresis, but the requirement of baseline data and uniformity of protein patterns make their results elusive (Ilhak and Arslan, 2007). Chromatographic techniques differentiate among origin of meat by their fatty acid and protein composition (Chou et al., 2007), enzyme-linked immunoassay by reactivity of specific antibodies with Abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the developed direct PCR method is coupled with RFLP assay which is much more desirable for molecular based meat identification, especially, in cases where large number of samples have to be processed as it does not require DNA sequencing and/or specialized equipment and reduces the cost and time for post-PCR processing of samples (Guan et al, 2019;Gargouri et al, 2021;Vaithiyanathan et al, 2021;Taha et al, 2021). It has been mostly applied for species discrimination in processed and unprocessed meat products because of its simplicity, quicker detection and reduced cost (Al et al, 2020;Asghar et al, 2022;Farag et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the developed direct PCR method is coupled with RFLP assay which is much more desirable for molecular based meat identification, especially, in cases where large number of samples have to be processed as it does not require DNA sequencing and/or specialized equipment and reduces the cost and time for post-PCR processing of samples (Guan et al, 2019;Gargouri et al, 2021;Vaithiyanathan et al, 2021;Taha et al, 2021). It has been mostly applied for species discrimination in processed and unprocessed meat products because of its simplicity, quicker detection and reduced cost (Al et al, 2020;Asghar et al, 2022;Farag et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In Islamic communities, eating donkey meat is forbidden, and mislabeling donkey meat as halal (permissible) is considered a heinous offense (Al- . Despite this, there are still cases of adulterated donkey in beef products in countries such as Pakistan (Asghar et al, 2021) and Tunisia (Gargouri et al, 2021). Zhao et al (2019b) tested the applicability of their developed authentication method on 46 commercial samples labeled as donkey burgers and found that four products contained horse meat and no donkey meat.…”
Section: Donkeymentioning
confidence: 99%
“…In Islamic communities, eating donkey meat is forbidden, and mislabeling donkey meat as halal (permissible) is considered a heinous offense (Al‐Ali & A, 2019). Despite this, there are still cases of adulterated donkey in beef products in countries such as Pakistan (Asghar et al., 2021) and Tunisia (Gargouri et al., 2021). Zhao et al.…”
Section: Overview Of the Research On Game Meat Authentication And Wil...mentioning
confidence: 99%
“…Pakistan is facing drastic peak in meat adulteration cases in past few years. The scenario clearly projects non-compliance of halal food laws [4]. This concrns the public health as sometimes edible and inedible meat can elicit the allergies, metabolic disorders and infectious diseases specially in sensitive and immunocompromised individuals [5].…”
Section: Introductionmentioning
confidence: 99%